Pembuatan Sistem Informasi Pengawas Ujian di Universitas Kristen Petra berbasis Website dan Facebook API - Monica Cindy; Andreas Handojo; Silvia Rostianingsih (Jurnal Infra, 2016)
Along with the development of Petra Christian University, the number of courses and students also grow significantly. Almost every program of study at Petra Christian University requires an invigilator. The way to spreading information and registration invigilator at Petra Christian University is still done manually. Each departement have difficulty in finding an invigilator, and students also have difficulty in finding information and vacancies about invigilator. Therefore, the need for a system such as a website that can be a liaison between students with department that require an invigilator.Based on the background of existing problems, the authors designed a web-based information systems that are in social media facebook using facebook API implementation and an email service for notifications. The information system is equipped with a feature list of the invigilator, feature to approve the invigilator, content overseen schedule, approve the schedule in case, invite the invigilator, notifications, import data from Excel files, and manage admin. The information system is made using CodeIgniter framework, PHP and HTML programming languge and MySQL database.Once the testing is done, a web-based information systems can run in facebook after login on facebook. Invigilator information system may be the link between courses that require an invigilator with students seeking jobs invigilator. Invigilator information systems can also provide email notification on facebook and students. This information system is getting the satisfaction score of 91.4% of respondents.